2020
DOI: 10.1038/s41418-020-00616-8
|View full text |Cite
|
Sign up to set email alerts
|

UBE2O targets Mxi1 for ubiquitination and degradation to promote lung cancer progression and radioresistance

Abstract: UBE2O, an E2/E3 hybrid ubiquitin-protein ligase, has been implicated in the regulation of adipogenesis, erythroid differentiation, and tumor proliferation. However, its role in cancer radioresistance remains completely unknown. Here, we uncover that UBE2O interacts and targets Mxi1 for ubiquitination and degradation at the K46 residue. Furthermore, we show that genetical or pharmacological blockade of UBE2O impairs tumor progression and radioresistance in lung cancer in vitro and in vivo, and these effects can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 32 publications
0
44
1
1
Order By: Relevance
“…The dysregulation of UBE2O and its clinical significance has been previously reported in several types of human cancers. UBE2O is highly expressed in lung cancer tissues, and its overexpression predicts poor prognosis 19 . The overexpression of UBE2O is confirmed in breast cancer tissues, and UBE2O expression is higher in patients with a poor prognosis and an increased risk of metastasis 18 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The dysregulation of UBE2O and its clinical significance has been previously reported in several types of human cancers. UBE2O is highly expressed in lung cancer tissues, and its overexpression predicts poor prognosis 19 . The overexpression of UBE2O is confirmed in breast cancer tissues, and UBE2O expression is higher in patients with a poor prognosis and an increased risk of metastasis 18 .…”
Section: Discussionmentioning
confidence: 99%
“…We randomly selected five high-power fields of view for each section. The intensity of staining was scored as 0 (negative), 1 (weak), 2 (moderate), and 3 (strong), and we scored the percentage of UBE2O positive tumor cells as 1 (0-25%), 2 (26-50%), 3 (51-75%), and 4 (75-100%) 19 . The IHC score was equal to the intensity score multiplied by the positive rate score.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deregulation of UBE2O has been associated with several human diseases, especially cancers. UBE2O could mediate Mxi1 ubiquitination and then promote lung cancer progression and radioresistance 25 . It has been reported that UBE2O could decrease the stability of MLL in a polyubiquitination-dependent manner, which results in aggressive leukaemia 26 .…”
Section: Discussionmentioning
confidence: 99%